Peran Harapan dalam Kepatuhan Pengobatan Kanker Kolorektal - M. Agung Rahmadi; Helsa Nasution; Luthfiah Mawa; Romaito Nasution; Milna Sari (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
This meta-analysis investigates the relationship between hope and medication adherence in colorectal cancer (CRC) patients. Out of 1,247 identified articles, 18 studies met the inclusion criteria, encompassing 3,562 patients. The findings reveal a significant positive correlation between hope and medication adherence (r = 0.42, 95% CI: 0.35-0.49, p < 0.001), with notable heterogeneity (I² = 76.4%, Q = 72.03, df = 17, p < 0.001). Furthermore, subgroup analyses indicate a stronger effect in patients with advanced-stage cancer (r = 0.49, 95% CI: 0.39-0.58) compared to those in various earlier stages (r = 0.38, 95% CI: 0.30-0.46, Q = 4.12, df = 1, p = 0.04). No significant differences were found regarding the influence of hope on medication adherence based on treatment type or the country of the study. Additionally, this research extends the findings of DiMatteo et al. (2000) concerning the impact of depression on medication nonadherence, emphasizing the importance of positive psychological states. Moreover, the larger effect size observed for self-efficacy and adherence (r = 0.31) reported by Hall et al. (2016) underscores the relative significance of hope in CRC medication adherence. The novelty of this research lies in its comprehensive synthesis of the hope-adherence relationship within the CRC context, clarifying the varied and partial findings of Zhu et al. (2017) and García-Torres et al. (2016). Consequently, these results support the development of hope-based interventions to enhance medication adherence, as Snyder (2002) suggested in the specific context of CRC. Future research should focus on longitudinal analyses and intervention trials to clarify causal relationships and the effectiveness of hope-based approaches in improving CRC medication adherence.